2018
DOI: 10.1021/acs.jnatprod.8b00044
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Determining the Relative Configuration of Furofuran Lignans by 1H NMR Spectroscopy

Abstract: An efficient H NMR spectroscopic approach for determining the relative configurations of lignans with a 7,9':7',9-diepoxy moiety has been established. Using the chemical shift differences of H-9 and H-9' (Δδ and Δδ), the configurations of 8-H and 8-OH furofuran lignans can be rapidly and conveniently determined. The rule is applicable for data acquired in DMSO- d, methanol- d, or CDCl. Notably, the rule should be applied carefully when the C-2 or C-6 substituent of the aromatic rings may alter the dominant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…7 The 1D and HSQC NMR data also exhibited the presence of two olefinic groups (δ H /δ C 6.82 (1H, td, J = fraction that showed the highest tyrosinase inhibition activity. 10 These results are consistent with those reported in prior literature. 11 μL of L-tyrosine (1.5 mM) was added to the reaction mixture (300 μL).…”
Section: Resultssupporting
confidence: 93%
“…7 The 1D and HSQC NMR data also exhibited the presence of two olefinic groups (δ H /δ C 6.82 (1H, td, J = fraction that showed the highest tyrosinase inhibition activity. 10 These results are consistent with those reported in prior literature. 11 μL of L-tyrosine (1.5 mM) was added to the reaction mixture (300 μL).…”
Section: Resultssupporting
confidence: 93%
“…The configuration of furofuran moiety in 1 was to be same as that of (+)-paulownin and (+)-1-hydroxysyringaresinol 1-glucoside based on the NMR data and optical rotation. 10,14) In addition, the trans/trans configuration of 7-H/8-OH and 7′-H/8′-H in the furofuran moiety was confirmed by comparison with the chemical shift differences. 15) Thus, the structure of 1 was determined (Fig.…”
Section: Introductionmentioning
confidence: 80%
“…10,14) In addition, the trans/trans configuration of 7-H/8-OH and 7′-H/8′-H in the furofuran moiety was confirmed by comparison with the chemical shift differences. 15) Thus, the structure of 1 was determined (Fig. 1 Tables 1 and 2) were almost identical to those of 5-methoxybalanophonin, which was isolated from the same plant source, 9) except for the additional glucose moiety [δ .…”
Section: Introductionmentioning
confidence: 80%
“…Furofuran lignans have their configuration well established in literature, according to Shao et al [66], the 7, 9 :7 , 9-diepoxi moiety of furofuran lignans of natural origin occurs in the cis-fused configuration. The experiments carried out have demonstrated that chemical deviations of the ∆δH-9 and ∆δH-9 are resulted of relative configurations of the C-7/C-8 and C-7 /C-8 .…”
Section: Isolation and Identification Of Lignansmentioning
confidence: 94%
“…The compounds secoisolariciresinol [63], pinoresinol-4-O-β-d-glucopyranoside [64], pinoresinol-4-O-β-d-apiofuranosyl-(1→2)-β-d-glucopyranoside [65], epipinoresinol-4-O-β-d-glucopyranoside [66] and were isolated from the fractionation of the crude ethanolic extract of thespecies Justicia aequilabris (Nees) Lindau [67] collected in the city of Puxinanã-PB, Brazil, registered in SisGen under the number: A35A42B. The compounds were identified by nuclear magnetic resonance and high-resolution mass spectrometry (HRMS).…”
Section: Isolation and Identification Of Lignansmentioning
confidence: 99%